Latar Belakang Keluarga terhadap Hasil Belajar Bahasa Indonesia - Hendrisman Hendrisman (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This study aims to determine the relationship of family background with the learning outcomes of Indonesian students in class XI of SMA Negeri 4 Payakumbuh. This study uses the correlation method. The population in this study amounted to 163 people. The sample is 27 people. Sampling was done by clater random sampling. The results showed the average value of the family background of students was 82 with good classification. The average value of student learning outcomes is 80 with good classification. There is a significant relationship between family background and student learning outcomes. Conclusion, the family background of students is related to the results of learning Indonesian, the better the family background of students, the better results of learning Indonesian students will be. Keywords: Family Background, Learning Outcomes, Indonesian Language